COMPASS for rapid combinatorial optimization of biochemical pathways based on artificial transcription factors - Gita Naseri (Nature Portfolio, 2019)
Metabolic engineering requires the balancing of gene expression to obtain optimal output. Here the authors present COMPASS – COMbinatorial Pathway ASSembly – which uses plant-derived artificial transcription factors and cloning of thousands of DNA constructs in parallel to rapidly optimise pathways.